The equation y = 16x 560 describes the number of calories in a recipe, where y is the total number of calories and x is the number of teaspoons of sugar added. The table shows the number of calories in another recipe, where y is the total number of calories and x is the number of teaspoons of honey added.How many calories are in a teaspoon of sugar, and how many are in a teaspoon of honey?



Teaspoons of honey 1 2 4 7
Total calories 504 568 696 888



A teaspoon of sugar has____ calories.

A teaspoon of honey has____ calories

Answers

Answer 1
Answer: a teaspoon of honey= 1 teaspoon of honey = 504 cal

a teaspoon of sugar = 1 teaspoon of sugar = 560+16 = 576 cal

y = 16x + 560 calories
 y=64x+440 calories

Add them and that's how you check. :)

(If that doesn't make sense, Sugar has 16 Cal. and Honey has 64 Cal.)


Related Questions

Randy ran 15.98 miles on Monday and 11.76 miles on Tuesday. How many more miles did Randy run on Monday than Tuesday?
In the neighborhood park there is a circular grassy picnic area, but half of the grass has died. The city wants to replant the grass, but needs to know the square footage of the damaged area. If the circular picnic area is 150 feet across, what is the square footage of the damaged area? Let π = 3.14.A) 471 sq. feet B) 8831.25 sq. feet C) 17662.5 sq. feet D) 35325 sq. feet
Y=kx+b A (1,-2) B (-2,-8) Linear functions!
Adam builds model rockets. Where he lives , his backyard is 12 feet below sea level. When he ignites his rocket, it flies a maximum of 350 feet straight up into the air before releasing its parachute. What is the altitude of adams rocket at its highest point, as measured from sea level?
I am a quadrangleI have 2 pairs of parallel sidesall of my angles are right anglesI am not a square

The perimeter of a triangle is 42 yards. The first side is 5 yards less than the second side, and the third side is 2 yards less than the first side. What is the length of each side?

Answers

Let the second side be equal to x Then the first side is x-5 The third side will be x-5-2 = x-7 Therefore you add all the following sides and equate it to 42 yards. Ie x+x+5+x-7 = 42 3x=44 X= 44/3 Therefore the second sides length is 44/3 The first sides length is 44/3 -5 = 29/3 The third side is 44/3 -7 = 23/3

4x+17/18-13x-2/17x-32+X/3= 7x/12-x+16/36​

Answers

Answer:To solve the equation 4x + 17/18 - 13x - 2/17x - 32 + x/3 = 7x/12 - x + 16/36, we can follow these steps:

1. Combine like terms on each side of the equation.

On the left side, we have 4x - 13x + x/3. Simplifying this, we get -8x + x/3.

On the right side, we have 7x/12 - x + 16/36. Simplifying this, we get -5x/12 - x + 4/9.

2. Get rid of any fractions by multiplying each term by the least common denominator (LCD).

The LCD of 3, 12, and 36 is 36. Multiply each term on both sides of the equation by 36 to eliminate the fractions.

3. Simplify and combine like terms.

On the left side, we have -8x + x/3, which becomes -24x + x^2/3 after multiplying by 36.

On the right side, we have -5x/12 - x + 4/9, which becomes -15x - 3x + 16 after multiplying by 36.

4. Move all terms to one side of the equation.

Combining like terms, we get -24x + x^2/3 = -18x + 16.

5. Multiply the entire equation by 3 to eliminate the fraction.

This gives us -72x + x^2 = -54x + 48.

6. Move all terms to one side of the equation again.

Combining like terms, we get x^2 + 18x - 48 = 0.

At this point, the equation is a quadratic equation. To solve it, we can either factor or use the quadratic formula.

Can someone help me plz​

Answers

x=12.9 rounded
Explanation: 30/7=x/3
90=7x
90/7=12.85...
X=12.9 when rounded to nearest tenth

Please solve the following quadratic equation and show your work: x^2 -x =30

Answers

Rewriting the equation as a quadratic equation equal to zero:
     x^2 - x - 30 = 0
We need two numbers whose sum is -1 and whose product is -30. In this case, it would have to be 5 and -6. Therefore we can also write our equation in the factored form
     (x + 5)(x - 6) = 0
Now we have a product of two expressions that is equal to zero, which means any x value that makes either (x + 5) or (x - 6) zero will make their product zero.
     x + 5 = 0  => x = -5
     x - 6 = 0  => x = 6
Therefore, our solutions are x = -5 and x = 6.

3 radical 7 - radical 7
= 3
why is this incorrect?

Answers

3√(7) - √(7)

Let x represent √(7), then you can rewrite the expression as 3x - x.

3x - x = 2x.  Now replace "x" with  √(7) and you get 2√(7).

The reason 3 is incorrect is because you are supposed to perform the operation (+, -, x, ÷) with the coefficients, not with the variable or radical.

Algebraically, you have to factor the square root of 7 to see why you're wrong:

3√(7)-√(7) = √(7)(3-1) = 2√(7)

Conceptually, think that any object - say an apple - represents the square root of seven.

So, you have three apples, and you take away one apple. You have two apples remaining, i.e. 2√(7)

The total number of laps needed to complete a bike marathon is 75. Kayla completed at least 68 laps. How many possible complete laps could Kayla have completed. Please show work. I'm offering lots of points for this question. Thanks you guys.

Answers

well she needs to complete 75 laps to complete the race so 75 is the upper limit.  She has completed at least 68 laps so the lower limit is 68.  so the number of laps she could have completed could be from 68 to 75 so the number of laps (x) can be reprented by this inequallity 68 < x < 75
well, I'm not sure if this is correct, it probably isn't, and I'm sorry if it isn't, but i think kayla could have completed 75 laps because there was only 75 laps in the race.